Antifungal properties of sodium peroxide and sodium hypochlorite as a denture cleanser for full acrylic denture in vitro - Subrata, Gantini (Universitas Padjadjaran, 2008)
Widely used materials are reported as denture cleansers are peroxide and hypochlorite. Many contradictions on the effectiveness of the commercial peroxide base solution against Candida albicans (C. albicans). Low concentration sodium hypochlorite (0.5%) is used as a household sanitizer. But it is still unknown whether it has an antifungal effect, what is the optimum concentration and contact time to destroy the yeast. The purpose of this study is to examine the antifungal efficacy of commercial peroxide-based soaking solution and low concentration sodium hypochlorite against C. albicans, to determine the optimum concentration and contact time, and at the end, to obtain an effective denture soaking solution which is safe to use, easy to get, affordable and could be used to destroy C. albicans on dentures. The research conducted was an in vitro practical test for surface disinfectant. Sixty plates of acrylic which were already incubated with C. albicans are immersed in peroxide and hypochlorite base soaking solution in different concentration and contact time. The result showed that peroxide base was not effective to C. albicans and hypochlorite base solution can destroy C. albicans in 10 minutes at a concentration of 0,125%. Thus, the use of low concentration sodium hypochlorite as a denture soaking solution can be suggested.